(untitled) (Research, Society and Development, 2022)
This work aimed to score the importance of recreational activities for the student’s work with children from zero to three years, seeking resources to find in attendance of the student the playful as strategic ways to trigger the intervention in the child process. The value of games and fun activities with effective subsidies for the construction of the knowledge held by the child. Demonstrate the importance of inclusion of recreational games, as a practical model of life and consciousness, aiming at a best practice in the development of the child with that games are playful learning instruments favouring effectively delivering speed in the process of behavior change and the acquisition of new behaviors. Thus, interventions with these fun activities are different means to achieve the objectives proposed. We seek the understanding of the importance of the games, toys and games within the educational psychology that we use as strategies in child development, favourable for cognitive development. Since the student will foster the child giving an aid to teaching situations are procedures that favor the understanding in the learning process. Considering the activities through fantasies will remain in the course of the child in its sessions, as the main source for the construction of knowledge. The student needs to possess through his investigations with the child, family and school to seek, recognize the main needs for use during in his speech with the child, because use of playful activities becomes essential for intervention with the child, to ensure the advancement of learning of children, already systematized at this age.